Efficient Esterification of Carboxylic Acids with Alcohols by Hydrogen Peroxide as a Novel Condensing Agent - Meshram, S.M.; Bharati, A.V.; Meshram, E.M. (Asian Journal of Chemistry, 2012)
Esterification of carboxylic acids with different alcohols has been achieved in presence of catalyst hydrogen peroxide and sulphuric acid. This method is free from disadvantages of base catalyst and high temperature. Hydrogen peroxide with sulphuric acid increases the yield up to 98 % with minimum side products. Several esters were synthesized by this method by condensing carboxylic acids (1) with alcohols (2) in presence of hydrogen peroxide and sulphuric acid.